2019
DOI: 10.9734/ca/2019/46914
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Age with Type of Congenital Heart Disease in Patients with Down Syndrome: A Single-center Study

Abstract: Background: Congenital heart disease (CHD) is commonly seen in patients with Down syndrome (DS) and is closely associated with morbidity and mortality. Maternal age is an established risk factor for DS. Objectives: The aim of the present study is to analyze the incidence of CHD in Down syndrome and the effect of maternal age on this incidence and the type of CHD. Materials and Methods: Six hundred and thirty-one patients with DS who were admitted to pediatric cardiology department, between December 2014 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…AVSD can occurs as a simplex trait, but also is associated with genetic syndromes such as Noonan syndrome, Holt-Oram syndrome and especially Down's syndrome. Previous studies found that AVSD were the most common CHDs in Down's syndrome, the incidence was from 9.6% to 46.4% (Mourato et al, 2014;Epçaçan et al, 2019). However, it remained ambiguous whether Down's syndrome was genetically linked with AVSD (Sailani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AVSD can occurs as a simplex trait, but also is associated with genetic syndromes such as Noonan syndrome, Holt-Oram syndrome and especially Down's syndrome. Previous studies found that AVSD were the most common CHDs in Down's syndrome, the incidence was from 9.6% to 46.4% (Mourato et al, 2014;Epçaçan et al, 2019). However, it remained ambiguous whether Down's syndrome was genetically linked with AVSD (Sailani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of maternal age on the association of CHD and DS is unclear; some studies reported a greater risk for CHDs in young mothers, [12,30] whereas others observed no maternal age effect [27,28] . We did not find any association between maternal age and the CHDs in our cohort of DS patients.…”
Section: Discussionmentioning
confidence: 99%